Campanella, Foucault, and Madness in Late-Sixteenth Century Italy - Scalzo, Joseph (The sixteenth century journal, 1990)
In his Madness and Civilization: A History of Insanity in the Age of Reason, Michel Foucault argues for a definition of insanity in the early modern period based on his dual concepts of the "discourse of madness," and the "animality of madness." From a study of Tommaso Campanella's heresy trial, which began in Naples in 1600, it seems that Foucault is partially correct. Campanella's heresy case suggests that both the concept of the "discourse of madness" and that of the "animality of madness" were evident in the Inquisition's judicial procedure. However, the issue of animality seems to have played a greater role in the outcome of Campanella's case, since such a definition was incorporated in the judicial torture which the Inquisition commonly used in cases in which the mental state of the accused was uncertain. In Campanella's case, in particular, such judicial torture was embodied in the Inquisition's veglia torture, meant to act as a final legal test for insanity. Campanella seems to have exploited this legally-defined view of insanity to his advantage, thereby saving himself from almost certain death.